2014
DOI: 10.1097/aci.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

An update on the pathogenesis of the upper airways in aspirin-exacerbated respiratory disease

Abstract: Chronic rhinosinusitis with nasal polyps is a major comorbid condition of AERD patients that is closely associated with severe asthmatic symptoms. Significant pathologic findings in nasal polyp tissues include intense eosinophilic inflammation, which is caused by elevated production of eosinophil-related cytokines and chemokines, specific immunoglobulin E responses to staphylococcal enterotoxins, and altered arachidonic acid metabolism. This could affect the current treatments and methodologies that are used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 53 publications
0
30
0
2
Order By: Relevance
“…Also, the production of PGE2 is reduced and COX-2 as well as E-prostanoid receptor subtype-2 are downregulated. 953 All of these effects add to an aggravation of the eicosanoid imbalance. Recently, gene profiling studies have suggested that periostin is the most upregulated gene in NP tissue of AERD patients.…”
Section: Viiic1h Crswnp Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the production of PGE2 is reduced and COX-2 as well as E-prostanoid receptor subtype-2 are downregulated. 953 All of these effects add to an aggravation of the eicosanoid imbalance. Recently, gene profiling studies have suggested that periostin is the most upregulated gene in NP tissue of AERD patients.…”
Section: Viiic1h Crswnp Pathophysiologymentioning
confidence: 99%
“…Recently, gene profiling studies have suggested that periostin is the most upregulated gene in NP tissue of AERD patients. 953,957 The complexity in the interaction of inflammatory mediators in AERD is underlined by the dysregulation of the PG2-dependent control of LT production in peripheral granulocytes. When compared to those of patients with ASA-tolerant asthma or those of controls, granulocytes of patients with AERD generate more LTB4 and cysLTs, and are resistant to the PGE2-mediated suppression of LT generation.…”
Section: Viiic1h Crswnp Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Periostin is also able to activate T cells and their differentiation into Th2 or neutrophils recruitment in bronchial mucosa [25,28]. Activated Th2 cells produce also IL-5 which intervenes in eosinophilic line development.…”
Section: Periostin and Bronchial Asthmamentioning
confidence: 99%
“…11 In recent years, there has been increasing interest in the potential role of cysLTs in the pathogenesis of CRSwNP. For instance, Steinke et al 11 showed that cysLTs levels are significantly increased in ECRS patients but not in non-ECRS patients and healthy controls. Our previous study also revealed the differential expression of cysLTs and its receptors (CysLT1R and CysLT2R) between the two CRSwNP subsets.…”
Section: Asian Pac J Allergy Immunol Doi 1012932/ap-030417-0063mentioning
confidence: 99%